AAACE Changed Our Lives: NPAC and Agricultural Communication in the '50s - Mason E. Miller (Journal of Applied Communications, 1995)
The recent death of Stanley Andrews, director of the National Project in Agricultural Communications (NPAC) during the 1950s recalls the excitement and energy of those times when the American Association of Agricultural College Editors (AAACE), the precursor of ACE, brought NPAC into existence. How NPAC came to be, and the various programs it developed with and for AAACE are outlined. Testimonials from editors and administrators of that day are presented to give some idea of the impacts NPAC had on agricultural editors, on ACE, and on editors' place in the land-grant system and in international communication.